Challenges associated with the management of gynecological cancers in a tertiary hospital in South East Nigeria - Iyoke CA; Ugwu GO; Ezugwu EC; Ezugwu FO; Lawani OL; Onyebuchi AK (Dove Medical Press, 2014)
Chukwuemeka Anthony Iyoke,1 George Onyemaechi Ugwu,1 Euzebus Chinonye Ezugwu,1 Frank Okechukwu Ezugwu,2 Osaheni Lucky Lawani,3 Azubuike Kanayo Onyebuchi3 1Department of Obstetrics and Gynaecology, University of Nigeria Teaching Hospital, Ituku-Ozalla, Enugu, 2Department of Obstetrics and Gynaecology, Enugu State University Teaching Hospital, Park Lane, Enugu, 3Department of Obstetrics and Gynaecology, Federal Teaching Hospital, Abakaliki, Ebonyi State, Nigeria Background: There are reports of increasing incidence of gynecological cancers in developing countries and this trend increases the need for more attention to gynecological cancer care in these countries. Objective: The purpose of this study was to describe the presentation and treatment of gynecological cancers and identify barriers to successful gynecological cancer treatment in a tertiary hospital in South East Nigeria. Methods: This study was a retrospective longitudinal analysis of the presentation and treatment of histologically diagnosed primary gynecological cancers from 2000 to 2010. Analysis was by descriptive and inferential statistics at the 95% level of confidence using Statistical Package for the Social Sciences version 17 software. Results: Records of 200 gynecological cancers managed during the study period were analyzed. Over 94% of cervical cancers presented in advanced stages of the disease and received palliative/symptomatic treatment. Only 1.9% of cervical cancer patients had radical surgical intervention, and postoperative mortality from these radical surgeries was 100%. Approximately 76% of patients with ovarian cancer had debulking surgery as the mainstay of treatment followed by adjuvant chemotherapy. Postoperative mortality from ovarian cancer surgery was 63%. Cutting edge cytotoxic drugs were not used as chemotherapy for ovarian and chorionic cancers. Compliance with chemotherapy was poor, with over 70% of ovarian cancer patients failing to complete the prescribed courses of chemotherapy. Most patients with endometrial and vulval cancers had only surgical treatment, as compliance with follow-up for adjuvant chemotherapy or radiotherapy was poor. Functional radiotherapy facilities were not available at the center during the study period, thereby necessitating external referrals to centers hundreds of kilometers away. Conclusion: Late presentation of cases, noncompliance with treatment regimens, lack of use of cutting edge cytotoxic drugs, the poor outcome of radical surgeries, and lack of a functional radiotherapy facility combined to create a very difficult gynecological cancer care environment at the study center. Keywords: gynecological cancer, management challenges, cancer surgery, chemotherapy